Motoric cognitive risk syndrome: Prevalence and cognitive performance. (31st December 2021) - Márquez, Isabel C; Garcia‐Cifuentes, Elkin; Velandia, Felipe Ramirez; Saavedra, Ana María; Borda, Miguel German; Chavarro‐Carvajal, Diego Andrés; Osuna, Margarita; Ailshire, Jennifer; Cano‐Gutierrez, Carlos Alberto
Abstract: Introduction: : Cognitive decline and dementia have a significant impact on the quality of life of older adults and their caregivers. Increasing and optimizing accessibility of clinical dementia risk assessment is important to set up preventive measures and reduce health care costs. Motoric Cognitive Risk Syndrome (MCRS) is a pre‐dementia stage where slow gait speed and subjective memory complaints are present, but where cognitive performance is adequate and without functional impairment. In addition to dementia, MCRS seems to increase the risk of having other geriatric outcomes including frailty, disability, falls and overall mortality. Methods: Data from the SABE Colombia study (Health, Well‐Being, and Aging) conducted in 2015 in community‐dwelling adults aged 60 years and older. Using the 4 aspects considered within the MCRS definition, we evaluated the presence of this syndrome and factors associated in this population with regression models. A sub‐sample of 19, 004 participants was obtained. Results: The multivariate analysis showed a prevalence of 5, 45% of MCRS. After adjusting for cofounding variables MCRS was associated with MMSE (OR 0.90, CI 0.82‐0.99; p 0.028) and frailty (OR 9.1, CI 3.26‐25.47, p 0.000; OR 21.38, CI 6.30‐72.57, p 0.000). Conclusion: This study found a prevalence of 5.45% of MCRS in Colombian older adults. We found an association between cognitive performance (MMSE), frailty and MCRS. Our results increase the awareness of a pre‐dementia stages different to Mild Cognitive Impairment (MCI), as these individuals are at greater risk than those with MCI to develop dementia.